Financial and legal bases for the formation of territorial communities capable budgets - D. V. Korobtsova; L. V. Mishchenko (Law and Safety)
The formation of UTC budgets requires not only the improvement of the structure of tax revenues, as well as the analysis of revenues, but currently the use of intergovernmental transfers as important additional revenues of UTC budgets in modern research is the subject of discussion.